Ketahanan Varietas Padi Lokal Asal Kabupaten Pesisir Selatan Terhadap Serangan Wereng Batang Coklat Nilaparvata lugens Stal. (Hemiptera: Delphacidae) - Dea Safitri; Novri Nelly; Arneti Arneti (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2025)
The use of resistant rice varieties remains a key component in managing the brown planthopper (BPH), Nilaparvata lugens Stål (Hemiptera: Delphacidae). However, information on the resistance of indigenous rice varieties from South Pesisir Regency, West Sumatra Province, Indonesia, is still limited. This study aimed to evaluate the resistance levels of several local rice varieties from South Pesisir Regency to BPH. The experiment was conducted under laboratory conditions using a completely randomized design with seven treatments and four replications. The treatments consisted of five local rice varieties (Sarai Sarumpun, Kutu, Bakwan, Banang Salai, and Bujang Marantau), with TN1 and IR74 used as susceptible and resistant controls, respectively. Seven-day-old rice seedlings were infested with second–third instar BPH nymphs. Variables observed included BPH attack symptoms, mortality, attack percentage, and attack intensity. The results showed significant variation in resistance among the tested varieties. Banang Salai exhibited the highest resistance, with 83.13% BPH mortality, 68.75% attack percentage, and 50.34% attack intensity, indicating a resistant response. In contrast, Sarai Sarumpun showed the lowest resistance, with only 25.94% BPH mortality and the highest attack intensity (90.52%), and was classified as highly susceptible. These findings demonstrate that Banang Salai is a promising local genetic resource for BPH resistance, highlighting the potential of indigenous rice varieties to support sustainable pest management.